(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article describes the features of the negative consequences of stress in the conditions of martial law in Ukraine. The main consequences of the negative impact of stress on the mental and physical health of students are considered. The theoretical analysis of scientific research shows that the problem of overcoming the negative consequences of stress has not been sufficiently studied in pedagogical theory, and therefore has not been properly reflected in the practical activities of educational institutions. Stress is an integral part of the life of any stratum of society, representatives of any profession, all age groups. The realities of the military conflict on the territory of Ukraine impose restrictions on the organization of the educational process, it is a challenge to provide training using not only health and training tools, but also informational ones for use during independent exercises with physical exercises to overcome the negative effects of stress, improve the nervous, respiratory, and cardiovascular conditions – vascular system. Physical education teachers in higher education institutions play an important role in helping to reduce the level of stress among students by using special exercises and methods aimed at relieving psycho-emotional stress. Taking into account the limited possibilities of the educational process, physical education teachers are responsible for choosing and implementing methods and tools that will contribute to increasing the effectiveness of learning, both online and during independent implementation by students. Research materials can be used in the educational process of educational institutions when teaching physical education. Physical education teachers are entrusted with the selection of methods and tools that can be used during training, online classes and independent implementation by students.